2014
DOI: 10.1186/1472-6882-14-236
|View full text |Cite
|
Sign up to set email alerts
|

Khz-cp (crude polysaccharide extract obtained from the fusion of Ganoderma lucidum and Polyporus umbellatus mycelia) induces apoptosis by increasing intracellular calcium levels and activating P38 and NADPH oxidase-dependent generation of reactive oxygen species in SNU-1 cells

Abstract: BackgroundKhz-cp is a crude polysaccharide extract that is obtained after nuclear fusion in Ganoderma lucidum and Polyporus umbellatus mycelia (Khz). It inhibits the growth of cancer cells.MethodsKhz-cp was extracted by solvent extraction. The anti-proliferative activity of Khz-cp was confirmed by using Annexin-V/PI-flow cytometry analysis. Intracellular calcium increase and measurement of intracellular reactive oxygen species (ROS) were performed by using flow cytometry and inverted microscope. SNU-1 cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In various cancer cells, chemotherapeutic agents induce apoptosis by increasing the level of ROS and activating NADPH oxidase (33,34). Excessive intracellular ROS production damages cellular function proteins and DNA, resulting in mitochondrial dysfunction and even apoptosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In various cancer cells, chemotherapeutic agents induce apoptosis by increasing the level of ROS and activating NADPH oxidase (33,34). Excessive intracellular ROS production damages cellular function proteins and DNA, resulting in mitochondrial dysfunction and even apoptosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that Khz induces apoptosis in human colon carcinoma HCT116 cells, accompanied by an increase in ROS, the activation of caspase 3 and increased intracellular Ca 2+ (24). In addition, our previous study demonstrated that crude polysaccharide extract obtained from the fusion of G. lucidum and P. umbellatus mycelia induces apoptosis by increasing intracellular Ca 2+ levels and activating the P38 and NADPH oxidase-dependent generation of reactive oxygen species in SNU-1 cells (25). In the present study, fusion of G. lucidum and P. umbellatus mycelium was perofmeed and used to treat MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Khz is a crude polysaccharide isolated from the fusion of G. lucidum and Polyporus umbellatus mycelia. This protein selectively induced apoptosis in cancer cells by increasing intracellular [Ca +2 ] to generate ROS [ 52 ]. Recently, the same group of investigators showed that Khz decreased proliferation and induced apoptosis on MCF-7 cells following similar mechanisms evidenced before.…”
Section: In Vitro Studiesmentioning
confidence: 99%